2012
DOI: 10.1093/neuonc/nor206
|View full text |Cite
|
Sign up to set email alerts
|

Arlm1 is a male-specific modifier of astrocytoma resistance on mouse Chr 12

Abstract: While many cancers show a sex bias, the genetic basis and molecular mechanisms underlying sex bias are not always clear. Astrocytoma and glioblastoma show male predominance in humans. We have shown previously that glial tumors forming in the Nf1-/+; Trp53-/+cis (NPcis) mouse model also show a sex bias in some genetic contexts. Using cross-species comparisons we have identified candidate male-specific modifiers of astrocytoma/glioblastoma. Linkage analysis of B6X(B6X129)-NPcis mice identifies a modifier of astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…High-grade gliomagenesis in the setting of combined NF1 and p53 loss has also been modeled in NPcis mice, which carry a genetic construct of tightly linked mutant alleles of NF1 and p53 (38). Similar to our results, when NPcis mice were maintained on a C57BL/6J background, high-grade gliomas occurred with a male predominance (12,39,40). Importantly, 129S4/SvJae mice were highly resistant to the gliomagenic effects of NPcis mutations.…”
Section: Discussionsupporting
confidence: 89%
“…High-grade gliomagenesis in the setting of combined NF1 and p53 loss has also been modeled in NPcis mice, which carry a genetic construct of tightly linked mutant alleles of NF1 and p53 (38). Similar to our results, when NPcis mice were maintained on a C57BL/6J background, high-grade gliomas occurred with a male predominance (12,39,40). Importantly, 129S4/SvJae mice were highly resistant to the gliomagenic effects of NPcis mutations.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also found an increased risk for need for therapy in females with NF1 and OPG, confirming recent studies suggesting that sex plays a role in the development of gliomas and neuronal dysfunction in patients with NF1. 21,22 A recent large multicenter study of visual outcomes in children with NF1 and OPG showed that at completion of chemotherapy, visual acuity improved in 32% of subjects, remained stable in 40%, and declined in 28%. 23 There are a number of limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mouse models also support roles for modifier genes in NF1. Astrocytoma resistance alleles were recently identified as spinal cord resistance to astrocytoma modifier 1 ( Scram1 ) and astrocytoma resistance locus in males 1 ( Arlm1 ) loci 38,51,52 . It is unclear whether disease modifier genes in NF1 are also relevant in NF1 -mutant sporadic tumours.…”
Section: Nf1 Genetics: Mutations and Modifiersmentioning
confidence: 99%